Factors influencing the in vitro growth and maintenance of several Vietnamese accessions of the duckweed Lemna aequinoctialis (Welw.) - Hoàng, Thị Như Phương (Springer Netherlands, 2024)
This study investigates the influence of various parameters on the efficiency of cultivating and preserving Lemna aequinoctialis duckweed samples in vitro, with the aim of minimizing time, labor, and storage expenses. The method addresses the issue of limited space and the risk of sample loss by storing multiple duplicates (more than one tube or flask per sample) in a space-efficient and cost-effective container. Due to the practical implications and capacity to decrease operating expenses, our results are helpful for large-scale implementation. Using a single frond resulted in a longer preservation effect compared to sample densities of three and five fronds. Initial samples can be cultured in nutrient solution with or without sugar, stored in tap water or nutrient solution, kept at a stable temperature of 25 ± 2°C or room temperature. The test tubes with duckweed were not covered, or covered by black paper up to the solution surface or higher. The outcomes demonstrated that all three duckweed samples (HNP_005, HNP_026, and HNP_031), whether grown in SSM or SFM media, were best preserved if the tubes were covered by black paper higher than the solution surface (CH) and can be kept at room temperature for at least 9 mo.